HUBUNGAN PEMAHAMAN KEPAHLAWANAN RADIN INTEN II TERHADAP KESADARAN SEJARAH SISWA SMA - Muhammad Arifin; Bahtiar Afwan (Swarnadwipa, 2021)
The purpose of this study is to describe the level of awareness, understanding and examine the factors that influence the level of awareness and understanding of students towards the heroism of Radin Inten II. The method used is a qualitative research method, namely a research method based on the philosophy of postpositivism, used to examine the condition of natural objects, by meeting face to face and interacting with people at the research site. The instruments used to collect data were a test of understanding the history of heroism by Radin Inten II and a historical awareness attitude questionnaire. Based on the results of the research, the level of historical awareness of class Xl students of SMA Negeri 1 Kotagajah is in the very good category with the average percentage shown for all indicators of 87 percent. While the level of student understanding of the heroism of Radin Inten II is said to be good, this is based on as many as 58 percent of 40 respondents successfully exceeding the KKM that has been determined by the school, namely 75. Factors that affect the level of understanding and awareness of the history of heroism of Radin Inten II are optimizing the learning process in class. From the results of this study, it can be concluded that the understanding and awareness of class XI students of SMA Negeri 1 Kotagajah towards the heroism of Radin Inten II is very good.